基于遗传算法的RPRPR五杆机构实现轨迹综合与分析 - 杨金堂; 孔建益; 熊禾根; 蒋国璋; 李公法; 廖汉元 (Jixie chuandong)
On the basis of the basic theory of five-bar mechanism and the theory of triangle stability,the RPRPR five-bar mechanism realizing accurately "the given tracks at random" is put forward in this paper.The optimization model of five-bar mechanism realizing accurately "the given tracks at random" is built.Then the numeric computing methods of compensation speed,acceleration and rotational speed,acceleration are analyzed and genetic algorithm is adopted to get the solution to optimization model.The instances indicate that the mechanism and the computing methods are correct.